N-Acetylcysteine Rescues Hippocampal Oxidative Stress-Induced Neuronal Injury via Suppression of p38/JNK Signaling in Depressed Rats - Fan, Cuiqin; Long, Yifei; Wang, Liyan; Liu, Xiaohang; Liu, Zhicheng; Lan, Tian; Li, Ye; Yu, Shu Yan (Frontiers in Cellular Neuroscience, 2020)
Progression of neuronal deterioration within specific brain regions is considered as one of the principal bases for the development of major depressive disorders. Therefore, protects and promotes the maintaining of normal structure and function of neurons might be a potential therapeutic strategy in the treatment of depression. Here, we report that the antioxidant, N-acetylcysteine (NAC), inhibited neuronal injury through it capacity to reduce oxidative stress and exerted antidepressant effects. Specifically, we show that antioxidant enzyme activity was significantly decreased in the hippocampal CA1 region of depressive rats, while treatment with NAC (300mg/kg, i.p.) produced neuroprotective effects against mitochondrial oxidative stress injuries and oxidative DNA damage in CA1 neurons of these rats. Moreover, NAC treatment alleviated neuronal injury resulting from neuroinflammation and apoptosis in depressed rats, effects which were associated reductions in dendritic spine atrophy and synapse deficits. These effects appear to involve a down-regulation of p38 mitogen-activated protein kinase (MAPK)-JNK signaling along with an up-regulation of ERK signaling within the hippocampal CA1 region. Moreover, this NAC treatment significantly ameliorated depression-like behaviors as indicated by performance in the sucrose preference and forced swim tests. Taken together, these results reveal the potential involvement of oxidative stress in the generation of depression. And, the antidepressant-like effects exerted by NAC may involve reductions in this oxidative stress that can result in neuronal deterioration. Such neuroprotective effects of NAC may indicate a potential therapeutic strategy for the treatment of stress-related depression.